A REVIEW ON MARKETING STRATEGIES AND SUSTAINABLE COMPETITIVE ADVANTAGE OF SMES IN THE MANUFACTURING SECTOR - Aliu, Mukhtar M.; Oni, Emmanuel O. (Covenant Journal of Entrepreneurship, 2020)
The problems associated with marketing strategies have assumed multifarious dimensions with wide implications in achieving business competitiveness, especially for small and medium enterprises (SMEs) in the manufacturing sector in Nigeria. This therefore calls for the adoption of marketing strategies in order to achieve successful competition and growth. This paper explores marketing strategies as a paradigm for sustainable competitive advantage for SMEs in the manufacturing sector. This paper is based on resource advantage theory which focuses on the control and ownership of distinctive quantity of competitive resources that foster sustainable competitive advantage and growth. Three major forms of marketing strategies were identified: cost leadership, product differentiation and market segmentation. The review exclusively makes use of systematic sampling in reviewing existing literatures on marketing strategies and sustainable competitive advantage. The findings reveals that good marketing companies win, sustain and grow customers by understanding customers need and designing customer-driven marketing strategies. Marketing strategies such as cost leadership, product differentiation and market segmentation are now widely used and practiced by established firms in a highly competitive market as a panacea for future competitiveness and long-term sustainability. Thus, this suggests that marketing strategies are good tools in achieving business competitiveness. Hence, business owners should put in place effective marketing strategies to help them gain sustainable competitive advantage over their competitors.